Functional redundancy and niche specialization in honeybee and Varroa microbiomes - Skičková, Štefánia; Kratou, Myriam; Svobodová, Karolína; Maitre, Apolline; Abuin-Denis, Lianet; Wu-Chuang, Alejandra; Obregón, Dasiel; Said, Mourad Ben; Majláthová, Viktória; Krejčí, Alena; Cabezas-Cruz, Alejandro (International microbiology, 2025)
The honeybee (Apis mellifera) is a key pollinator critical to global agriculture, facing threats from various stressors, including the ectoparasitic Varroa mite (Varroa destructor). Previous studies have identified shared bacteria between Varroa mites and honeybees, yet it remains unclear if these bacteria assemble similarly in both species. This study builds on existing knowledge by investigating co-occurrence patterns in the microbiomes of both Varroa mites and honeybees, shedding light on potential interactions. Leveraging 16S rRNA datasets, we conducted co-occurrence network analyses, explored Core Association Networks (CAN) and assess network robustness. Comparative network analyses revealed structural differences between honeybee and mite microbiomes, along with shared core features and microbial motifs. The mite network exhibited lower robustness, suggesting less resistance to taxa extension compared to honeybees. Furthermore, analyses of predicted functional profiling and taxa contribution revealed that common central pathways in the metabolic networks have different taxa contributing to Varroa mites and honeybee microbiomes. The results show that while both microbial systems exhibit functional redundancy, in which different taxa contribute to the functional stability and resilience of the ecosystem, there is evidence for niche specialization resulting in unique contributions to specific pathways in each part of this host-parasite system. The specificity of taxa contribution to key pathways offers targeted approaches to Varroa microbiome management and preserving honeybee microbiome. Our findings provide valuable insights into microbial interactions, aiding farmers and beekeepers in maintaining healthy and resilient bee colonies amid increasing Varroa mite infestations.
Keywords: mikrobiota; Networks; Varroa destructor; RNA ribozomální 16S; Apis mellifera; Bacteria; Animals; Microbiomes; Community assembly; Microbiota; Varroidae; zvířata; včely; RNA, Ribosomal, 16S; Bees